FAKTOR - FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS BANDAR KHALIPAH TEMBUNG - ALDA HALIMAH LISNA; HEPPY JELITA SARI BATUBARA (LP2MTBM MAKARIOZ, 2021)
The prevalence of Anemia in pregnant women in Indonesia reaches 63,5% and in Bandar Khalipah Tembung CommunityHealth Center increased from 19,3% (2018) to 24,9% (2019). Pregnant women with anemia will experience an increased riskof morbidity and mortality. This study was to determine the factors that affects the incidence of anemia in pregnant women.Analytical observational study with cross sectional design using secondary data from medical records from January toDecember 2019. The subjects of this study were 44 pregnant women in their third trimester at the Bandar Khalipah TembungCommunity Health Center with total sampling. Data analysis used the chi-square test. The results showed that the mostpregnant women with multigravida were 15 people (55,6%), low education level were 17 people (77,3%) and low economicstatus were 14 people (63,6%). Factors related to incidence of anemia in pregnant women are educational level (p-value0,001) and economic status (p-value 0,005). Educational level and economic status are factors that affects the incidence ofanemia in pregnant women.